Security against Timing Analysis Attack - Deevi Radha Rani; S Venkateswarlu (International Journal of Electrical and Computer Engineering (IJECE), 2015)
Timing attack is the type of side-channel attack involves the time taken to complete critical operations. Securing crypto processor from timing attack is critical issue. This paper implements the Bernstein’s Timing Attack and timing attack based on hamming weight. The countermeasures of Bernstein’s Timing attack are implemented in our experimental test bed and their performance is compared.  This paper also proposes the key recovery method based on timing attack using hamming weight of the key.